Malvidin’s Effects on Rat Pial Microvascular Permeability Changes Due to Hypoperfusion and Reperfusion Injury - Lapi, Dominga; Chiurazzi, Martina; Di Maro, Martina; Mastantuono, Teresa; Battiloro, Laura; Sabatino, Lina; Ricci, Serena; Di Carlo, Angelina; Starita, Noemy; Guida, Bruna; Santillo, Mariarosaria; Colantuoni, Antonio (Frontiers in Cellular Neuroscience, 2016)
The present study was aimed to evaluate the malvidin’s protective effects on damage induced by 30 min bilateral common carotid artery occlusion (BCCAO) and 60 min reperfusion in rat pial microcirculation. Rat pial microcirculation was observed using fluorescence microscopy through a closed cranial window. Western blotting analysis was performed to investigate the endothelial nitric oxide synthase (eNOS), phosphorylated eNOS (p-eNOS) and matrix metalloproteinase 9 (MMP-9) expression. Moreover, MMP-9 activity was evaluated by zymography. Finally, neuronal damage and radical oxygen species (ROS) formation were assessed. In all animals, pial arterioles were classified in five orders of branching according to Strahler’s method. In hypoperfused rats, 30 min BCCAO and 60 min reperfusion caused a decrease in arteriolar diameter, an increase in microvascular leakage and leukocyte adhesion, accompanied by decreased capillary perfusion and red blood cell velocity (VRBC). Moreover, marked neuronal damage and evident ROS generation were detected. Conversely, malvidin administration induced arteriolar dilation in dose-related manner, reducing microvascular leakage as well as leukocyte adhesion. Capillary perfusion and VRBC were protected. Nitric oxide synthase inhibition significantly attenuated malvidin’s effects on arteriolar diameter. Western blotting analysis revealed an increase in eNOS and p-eNOS expression, while zymography indicated a decrease in MMP-9 activity after malvidin’s administration. Furthermore, malvidin was able to prevent neuronal damage and to decrease ROS generation. In conclusion, malvidin protects rat pial microcirculation against BCCAO/reperfusion injury, preventing blood-brain impairment and neuronal loss. Malvidin’s effects appear to be mediated by eNOS activation and scavenger activity.